The Effects of Adding CaCOᴣ and Glycerol as Filler in The Synthesis of Bioplastic Made from Corn Starch - Safira, Ajeng Listiani; Suffah, Nurullia; Hendrawati, Tri Yuni; Astuti, Erna (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2024)
Plastic is one of the items widely used by the world's population, including in industry. Apart from being cheaper, plastic also has the advantage of being waterproof and having good strength to withstand the load carried. However, plastic has weaknesses in the decomposition process and can cause environmental pollution. Corn has a high percentage of starch content and is easy to cultivate in Indonesia, so corn has the potential to become one of the raw materials used in making bioplastics to reduce the plastic waste produced. This research aims to determine the effect of adding CaCOᴣ and glycerol fillers in synthesizing bioplastics from corn starch. The method applied in this research is pouring the solution. Based on research, the reaction to make bioplastic from corn starch with CaCO3 filler and glycerol is an esterification reaction. The higher the CaCO₃ content in bioplastics, the smaller the percent elongation value produced, the tensile strength properties will decrease, and this will result in the %w loss value decreasing. The low tensile strength is due to the presence of empty holes in the bioplastic product. Meanwhile, more glycerol will cause an increase in the percent elongation value, a decrease in tensile strength, and easy degradation. The bioplastic that has specification close to SNI standards was obtained using 5 ml of glycerol and 2 grams of CaCO₃ for 100 g of corn starch.